Case Study : RD Alumglass / Danish Daniel Budriz Roslan - Budriz Roslan, Danish Daniel (2021)
In the Case Study assignment, students are required to analyse a real business situation. In this case, I have chosen RD Alumglass, owned by Mr. Roslan in Kelantan. I once met him several times to gather information about his business and see the characteristics of his success in the field of entrepreneurship. The idea to open this business was inspired by his uncle that run this type of business. First, RD Alumglass is the company name, it is short form from Roslan Design Aluminium and Glass. He was inspired by his uncle. When he was a teenager, he works with uncle and learn about glass, aluminium, and making picture frame. He started this since 1996 until now and he is expert in making window, mirror, sliding door and so on that related to aluminium and glass. This store is located at Lot 2406 -A Kampung Tini Jalan Pasir Hor 15100 Kota Bharu Kelantan.